Teaching English in ASEAN: The voices of English teachers in ASEAN nations - Waterworth, Peter (Indonesian Journal of Applied Linguistics, 2016)
The effective teaching of the English language is regarded as an essential element in the creation of a culturally vibrant, economically sound and socially stable ASEAN community. The ASEAN region is populated by a culturally diverse collection of peoples with very different and complex linguistic histories, some of which included a strong English component. This paper examines the opinions and understandings of teachers of English in eight of the ten ASEAN nations. It arose out of a research study of English teaching in ASEAN being conducted jointly by Universitas Pendidikan Indonesia and CfBT Brunei. Although the teachers differed in their levels of competence in English and in their experience of local, national and international culture, they shared a remarkably similar story in attempting to provide the best instruction they possibly could to their students. As non-native speakers of English, they shared the responsibility of representing not only the English language but also the culture of first language English speakers to their non-native speaking students. The conflicts and tensions of their roles were identified and examined. The study concluded that teachers need support in their intercultural role as well as in their pedagogical responsibilities. Teachers reported that their students had little knowledge or appreciation of the ASEAN community or of the importance of their own capacity to speak English in it.